Prevalence and factors associated with psychological violence against married women in Thiruvananthapuram district, Kerala - Raheela, Ameena Subair; Indu, Pillaveetil Sathyadas (International Journal Of Community Medicine And Public Health, 2020)
Background: The distribution and determinants of violence against women may vary in time across the region and within the region. It results in women’s physical and psychological sufferings and the final impact will reflect in the health system. Kerala is one of the leading states in India for female literacy and health indices. Still different forms of domestic violence including physical, psychological, economical and sexual violence are prevailing as a public health problem. Among the various domains this study measured the prevalence of psychological violence and identified associated factors, among married women aged 18-55 years in Thiruvananthapuram district. Methods: A community based cross-sectional study was conducted between January and May 2017. Sample size calculated was 270. Multistage cluster sampling was done. Tool used was semi structured questionnaire; conducted house visits and direct interview. Psychological violence was measured using modified scale validated in local language. Results: The life time prevalence of psychological violence was 25.2% (95% CI 20.2-30.6). The predictors of psychological violence found were care obtained during pregnancy (AOR 0.107), household structure (AOR 7.8), in laws’ satisfaction with marriage (AOR 0.046), less communication with own family (AOR 8.6) and partner’s parents quarrel (AOR 31.3). Conclusions: Psychological violence is still prevalent in the community. The associated factors include those relating to habit of the partner, house hold conditions, marital elements and family environment. The study identified nurturing friendly atmosphere in the family and improving familial bond as the core strategy to prevent psychological violence. Similar studies are recommended in each setting separately since risk factors varies with change in settings.